Deregulation of Network Industries: What's Next? - Peltzman, Sam; Winston, Clifford (Rowman & Littlefield Publishers, 2011)
Although the airline, railroad, telecommunications, and electric power industries are at very different stages in adjusting to regulatory reform, each industry faces the same critical public policy question: Are policymakers taking appropriate steps to stimulate competition or are they turning back the clock by slowing the process of deregulation? This volume addresses that issue and identifies the next steps that policymakers should take to enhance public welfare in the provision of these services. Each chapter identifies the central policy issues that have arisen in each industry as it undergoes transformation to a deregulated environment. The authors reveal the flaws in the residual regulations and make the case for faster and more comprehensive deregulation. A concluding chapter identifies how interest groups continue to exert influence on regulatory agencies and on Congress, potentially undermining deregulation. The papers included here were initially presented in December 1999 at a conference sponsored and organized by the AEIBrookings Joint Center for Regulatory Studies.